Analisis Literatur tentang Perkembangan Konsep Manajemen Operasi dalam Industri Modern - Muhammad Faisal Haririe Nst; Sawaludin Harahap; Ansory Ramadhan; Fahrinsal Sitorus; Arsyadona Arsyadona (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Industrial transformation driven by digital revolution, sustainability demands, and global market dynamics has significantly reshaped the paradigm of operations management. This study aims to analyze the evolution of operations management concepts within the context of modern industry through a systematic literature review of scholarly publications from the last five years (2020–2025). A qualitative research approach based on literature study was employed, involving a selection of peer-reviewed articles sourced from reputable academic databases such as Scopus and ScienceDirect. The findings indicate that operations management has expanded from a technical function to a strategic one, emphasizing process digitalization, sustainability integration, and the combination of lean and agile operations. Concepts such as the Internet of Things (IoT), big data analytics, green supply chains, and leagile systems have emerged as key pillars in the current operational landscape. The study concludes that modern operations management is multidimensional, adaptive, and strategically driven, thereby requiring interdisciplinary collaboration for future development. These insights are expected to contribute to both theoretical advancements and practical policy implications in the field of industrial operations.